CD274 (PD-L1) genomic change: another marker for small-cell lung cancer? - Inoue, Yusuke; Suda, Takafumi; Sugimura, Haruhiko (Translational Cancer Research; Vol 6, Supplement 1 (February 28, 2017): Translational Cancer Research, 2017)
Small-cell lung cancer (SCLC) is an extremely aggressive subtype of lung cancer, which accounts for approximately 15% of all lung cancer cases. The disease is characterized by rapid growth and early metastasis to distant organs; thus, most patients with SCLC are diagnosed in advanced stages. Despite frequently observed good initial responses to systemic chemotherapy, almost all advanced SCLC cases eventually relapse, becoming nonresponsive to chemotherapy within months, and the prognosis is dismal. Compared with non-small-cell lung cancer (NSCLC), there have been fewer advances in the treatment of SCLC in the past few decades.